Environmental evolution of coastal regions in northern Beibu Gulf, South China, based on sedimentary elemental records and carbon-nitrogen isotope composition - Jing Guo; Zihan Pan; Xiaomin Yan; Man Wu; Hengtong Qiu; Wanyi Li; Wenlong Huang; Di Wu; Baoming Xue; Zhiming Mo; Guilin Xu (International Journal of Sediment Research, 2025)
Elucidating the historical variation of biogenic elements and source provenance in coastal areas is crucial to better understand environmental evolution and organize ecological management. In this study, the spatiotemporal distribution of biogenic elements (carbon (C), nitrogen (N), phosphorus (P), and silicon (Si)), and carbon and nitrogen isotopes (δ13C and δ15N), respectively in sediment were explored to illustrate elemental changes and determine sources of sedimentary organic matter (SOM) in the coastal regions of northern Beibu Gulf (CNBG). C, N, and P contents exhibited a general decreasing pattern from estuaries to offshore areas, probably due to terrigenous inputs and sediment textures. Since Si was mainly associated with diatoms, lower Si was attributed to the depression of phytoplankton growth by oyster beds in estuaries of Fangcheng Bay and the Maowei Sea. Based on a δ13C and δ15N three-end-member mixing model, it revealed that the average contribution of terrigenous plants and shellfish biodeposition for SOM were 56.00% and 22.39% in the intensive mariculture region (IMR), indicating that terrestrial sources and mariculture biodeposits played a prominent role as SOM sources. Additionally, according to three lead 210 (210Pb) dated sediment cores, it was found that elemental contents and elemental burial rates increased along with the coastal development after 1980s, particularly since 2006 when the Beibu Gulf Economic Zone was established. Multiple Linear Regression results showed that C and N contents and sedimentation rates were responsible for the variation of carbon burial rates during the past decades. More importantly, the significant positive relation between elemental contents and population, and gross domestic product (GDP) growth further proved a close relation between environmental evolution in the CNBG and the socioeconomic development of Guangxi Province. Moreover, the different trends of SOM source contribution for three sediment cores demonstrated the evolution characteristics among different coastal environments. The elevated δ13C and δ15N manifested the increasing contribution of marine phytoplankton (46.83%–69.33%) to SOM in Sanniang Bay recently, where frequent occurrence and decomposition of algal blooms resulted in more SOM. The dominant fraction of terrestrial sources (76.50% ± 13.27%, where ± indicates a standard deviation bound) to SOM in Lianzhou Bay implied the significant impacts of riverine inputs and fishing activities during the last century. This study indicates human activities have led to the continuous increase in nutrients, which has caused ecological risks such as algal blooms in the CNBG, thus, the mitigation of coastal eutrophication needs close attention.